Modelling of Aerosol Parameters Retrieval Algorithm Based on Mie Scattering Lidar: APRA - Ruangrungrote*, Siriluk; Chanthrasre, Suthipan; Intasorn, Arunee (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The software package APRA (Aerosol Parameters Retrieval Algorithm) was written in MATLAB R2008a. It allows the possibilities to determine the vertical profiles of tropospheric range corrected signals, depolarization ratios, aerosol volume backscattering coefficients and aerosol volume extinction coefficients from the measured dataset of Mie Scattering Lidar. In order to monitor the program efficiency, both pseudo and real data were used for the program demonstration, and finally the retrieved results from raw data of Mie Scattering Lidar measurement in Phimai district, Nakhon Ratchasima province of Thailand were performed and subsequently compared to the previous results retrieved manually from the same data. Keywords: Software package, APRA, pseudo data, Fernald - Klett method, Mie Scattering Lidar *Corresponding author: E-mail: sirilukr@swu.ac.th